From Lactose to Alkyl Galactoside Fatty Acid Esters as Non‐Ionic Biosurfactants: A Two‐Step Enzymatic Approach to Cheese Whey Valorization. Issue 1 (2nd January 2023) - Semproli, Riccardo; Simona Robescu, Marina; Sangiorgio, Sara; Pargoletti, Eleonora; Bavaro, Teodora; Rabuffetti, Marco; Cappelletti, Giuseppe; Speranza, Giovanna; Ubiali, Daniela
Abstract: A library of alkyl galactosides was synthesized to provide the "polar head" of sugar fatty acid esters to be tested as non‐ionic surfactants. The enzymatic transglycosylation of lactose resulted in alkyl β‐D‐galactopyranosides, whereas the Fischer glycosylation of galactose afforded isomeric mixtures of α‐ and β‐galactopyranosides and α‐ and β‐galactofuranosides. n ‐Butyl galactosides from either routes were enzymatically esterified with palmitic acid, used as the fatty acid "tail" of the surfactant, giving the corresponding n ‐butyl 6‐ O ‐palmitoyl‐galactosides. Measurements of interfacial tension and emulsifying properties of n ‐butyl 6‐ O ‐palmitoyl‐galactosides revealed that the esters of galactopyranosides are superior to those of galactofuranosides, and that the enantiopure n ‐butyl 6‐ O ‐palmitoyl‐β‐D‐galactoside, prepared by the fully enzymatic route, leads to the most stable emulsion. These results pave the way to the use of lactose‐rich cheese whey as raw material for the obtainment of bio‐based surfactants. Abstract : (Bio)Surfing the wave of lactose upcycling . Sugar fatty acid esters were prepared starting either from lactose through a two‐step enzymatic approach catalyzed by immobilized β‐galactosidase from Aspergillus oryzae and immobilized CalB (Novozym® 435), or from galactose through a two‐step chemoenzymatic strategy. n ‐Butyl galactoside fatty acid esters were shown to possess good interfacial features, being the pure β‐anomer prepared by the fully enzymatic route the best emulsifier.